WEATHER MONITORING MODEL BASED ON SATELLITE DATA(MODEL PEMANTAUAN CUACA BERDASAR PADA DATA SATELIT) - Idung Risdiyanto (PERHIMPI (Indonesian Association of Agricultural Meteorology), 2008)
Weather monitoring model is closely related to the problem of objective analysis of the field of meteorology. The amount of meteorological data is quite substantial and hence the processing of these data is one of primary problems is dynamic meteorology. Therefore, a weather system model must consider atmospheric process, which can be built by mechanistic model rather than statistical approach. Integration of numerical model and spatial model will produce spatial weather information. It should be managed in one computerized system called as an information system for weather monitoring. The approach of the research was divided into five tasks. First task was satellite data capturing and extracting, second was development of numerical modeling based on dynamic and thermodynamic of atmospheric process, third was integration of numerical modeling and geographic information system in the spatial model, fourth was to develop graphical user interface and the fifth task was application of system in the real-world. Temporal resolution of this model is one day, however, in reality weather is temporal state of atmosphere condition that change any time. Moreover, this model only describes weather condition when data satellite on the day could be captured. Therefore, to increase the temporal resolution of this model, the input data could be added or integrated with other satellite data such as GMS satellite that has one-hour temporal resolution. Spatial resolution in this model is 50x50 kilometers square for global and 8x8 kilometers for regional area. Actually, for the spatial resolution, this model has been prepared as NOAA’s spatial resolution. This model cannot simulate vertical distribution of atmosphere, so, it does not give information about relative humidity and precipitation. If air movement in vertical area could be simulated, the dew point temperature and lighting condensation level would be known therefore the relative humidity and precipitation could be predicted.